Combating Micronutrient Deficiency and Enhancing Food Functional Quality Through Selenium Fortification of Select Lettuce Genotypes Grown in a Closed Soilless System - Pannico, Antonio; El-Nakhel, Christophe; Kyriacou, Marios C.; Giordano, Maria; Stazi, Silvia Rita; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2019)
Selenium (Se) is an essential trace element for human nutrition and a key component of selenoproteins having fundamental biological and nutraceutical functions. We currently examined lettuce biofortification with Se in an open-gas-exchange growth chamber using closed soilless cultivation for delivering Se-rich food. Morphometric traits, minerals, phenolic acids and carotenoids of two differently pigmented Salanova cultivars were evaluated in response to six Se concentrations (0 - 40 μM) delivered as sodium selenate in the nutrient solution. All treatments reduced green lettuce fresh yield slightly (9%), while decrease in red lettuce was observed only at 32 and 40 μM Se (11% and 21% respectively). Leaf Se content increased in both cultivars, with the red accumulating 57% more Se than the green. At 16 μM Se all detected phenolic acids increased, moreover a substantial increase in anthocyanins (184%) was recorded in red Salanova. Selenium applications slightly reduced the carotenoids content of green Salanova, whereas in red Salanova treated with 32 μM Se violaxanthin + neoxanthin, lutein and β-cryptoxanthin spiked by 38.6%, 27.4% and 23.1%, respectively. Lettuce constitutes an ideal target crop for selenium biofortification and closed soilless cultivation comprises an effective tool for producing Se-enriched foods of high nutraceutical value.